Methodological choice and design scholarship, policy and practice in social and educational research - Markauskaite, Lina.; Freebody, Peter; Irwin, Jude.; SpringerLink (Online service). (Dordrecht Netherlands Springer, 2011)
Beginning and well-seasoned researchers alike face major challenges in understanding the complexities of research designs arising from within and across methodological paradigms as well as in applying them in ways that maximize impact on knowledge, practice and policy. This volume offers crucial reinterpretations of established research methodologies in light of contemporary conditions. It also presents a critical introduction to some contemporary research approaches yet to gain general recognition. It charts and analyzes the conceptual and practical complexities of a variety of research designs for contemporary educational and social work research, providing readers what they need not only to design technically sound and coherent research studies but also to develop methodologically innovative research projects that cross the boundaries between different methodological traditions to the benefit of scholarship, policy, and practice.
Part I Introduction and foundations: 1 Bridging and blending disciplines of inquiry: doing science and changing practice and policy: Lina Markauskaite, Peter Freebody and Jude Irwin, 2: Knowledge and epistemology in scholarship, practice and policy: research-as-science and research-as-project: Peter Freebody, Lina Markauskaite and Jude Irwin, Part II Research approaches for innovation and change: 3: Design-based research: Peter Reimann, 4 Design-based research: reflections on some epistemological issues and practices: Richard Walker, 5: Action research in education and social work: Susan Groundwater-Smith and Jude Irwin, 6; Action research and professional learning: some reflections on inquiries that advance professional knowledge and practice: Robyn Ewing, 7: Ethnomethodological research in education and the social sciences: studying ?the business, identities and cultures? of classrooms: Peter Freebody and Jill Freiberg, 8 Drama education, ethnomethodology and ?industrious chatter?: Michael Anderson, 9: Negotiated ethnography: the possibilities for practice: Debra Hayes, 10: Provoking change ? the role of research in institutional learning and organisational change: Ken Johnston, 11 Drawing on the arts, transforming research: possibilities of arts-informed perspectives: Ardra L. Cole and J. Gary Knowles, 12 Investigating the liminal in professional education through arts-informed research: Robyn Ewing, Part III Classical research approaches in new social and political contexts, 13 Historical analysis: new approaches to postcolonial scholarship and the subcontinent: Tim Allender, 14 Postcolonial scholarship in social justice research: Ruth Phillips, 15 Analysing policy as discourse: methodological advances in policy analysis: Susan Goodwin, 16 Policy analysis and social transformation: making connections between policy fields and contemporary social life: Amanda Elliot, 17 The challenge of comparative research: a critical introduction: Anthony Welch, 18 Know thyself: culture and identity in comparative research: Nigel Bagnall, 19 Quantitative modelling of correlational and multi-level data in educational research: a construct validity approach to exploring and testing theory: Andrew J. Martin, Jasmine Green, Susan Colmar, Gregory A. D. Liem and Herbert W. Marsh, 20 Quantitative modelling of experimental data in educational research: current practice and future possibilities; Paul Ginns, Part IV Methodological frontiers, challenges and future directions, 21 Digital knowledge and digital research: what does eResearch offer education and social policy?: Lina Markauskaite, 22 Emerging methodological challenges for educational research: Peter Goodyear, 23: Challenges and futures for social work and social policy research methods Barbara Fawcett, Susan Goodwin and Ruth Phillips, 24: Research frontiers and border-crossings: methodology and the knowledge industry: Patrick Brownlee and Jude Irwin, Subject index, Author index.
Electronic reproduction.
Keywords: Education -- Research -- Methodology; Electronic books